Description of Visual Acuity and Refractive Arrangements in Patients Post Cataract Operation at Jec Orbita Makassar Eye Hospital in 2022 - Yulia Nugra; Zulfikri Khalil Novriansyah; Hikmah Hiromi R; Nur Aulia Amir; Ruslinah, Ruslinah (Sean Institute, 2024)
Survey results show that the main cause of blindness is cataracts. The only definitive therapy for cataract patients is surgery. However, not all patients who have undergone surgery will achieve the desired visual improvement and therefore affect the patient's quality of life. To determine the description of visual acuity and refractive errors in patients after cataract surgery at the JEC-Orbita Makassar Eye Hospital in 2022. This research is a descriptive study with a cross sectional approach using secondary data from the medical records of patients who have had cataract surgery at the JEC Eye Hospital -Orbita Makassar in 2022. Results: Visual acuity at H+1 post-surgery mostly showed blind vision (32.3%), at H+7 post-surgery most showed normal vision (43%), and at H+30 post-surgery the majority showed normal vision (68.8%). The refractive errors found were 17.2% hypermetropia, 10.8% AHS, 9.7% AMS, 9.7% AM, 8.6% AHC, and 1.1% myopia. Conclusion: Visual acuity after cataract surgery shows significant improvement and continues to improve with increasing length of control time. Large parts of post-operative refractive error show hypermetropia, then AHS, AMS, AM, AHC and myopia sequentially.